2014
DOI: 10.22146/ijc.21238
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation and Acetylation of Ursolic and Oleanolic Acids Isolated from <i>Fragraea fragrans</i> fruits; Antiproliferation of P388 Leukemia Cells

Abstract: An interesting natural product chemistry aspect of Fragraea fragrans is that their fruits are richness with ursolic acid and its isomer oleanolic acid (3.05% of dried powder). As our continuous work on these inseparable structural isomeric triterpenes, this paper reports that 51.0% of inseparable 3-oxo-ursolic[3-oxo-oleanolic] acids and 48.6% of inseparable 3-acetyl-ursolic [3-acetyl-oleanolic] 52,8% asam 3-okso-ursolat[3-oxo-oleanolat] dan 48,6% asam 3-asetil-ursolat[3-asetil-oleanolat] telah berhasil d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…White amorphous powder. 1 H NMR (500 MHz, Acetone‑ d 6 ) and 13 C NMR (125 MHz, Acetone‑ d 6 ) data were consistent with those reported in the literature ( Basir et al, 2014 ).…”
Section: Resultssupporting
confidence: 89%
“…White amorphous powder. 1 H NMR (500 MHz, Acetone‑ d 6 ) and 13 C NMR (125 MHz, Acetone‑ d 6 ) data were consistent with those reported in the literature ( Basir et al, 2014 ).…”
Section: Resultssupporting
confidence: 89%
“…Compounds obtained as pure isolates included friedelin (compound 1) (Mann et al, 2012), 3β-acetoxyurs-11-en-13β,28-olide (compound 2) (Raza et al, 2015), betulinic acid (compound 7) (Lee et al, 2005), kaempferol-3-O-rutinoside (nicotiflorin) (compound 10) (Erosa-Rejón et al, 2010), and 3,4-dihydroxycinnamic acid (caffeic acid) (compound 13) (Zhou et al, 2017). In accordance with previous reports (Basir et al, 2014), 3β-O-acetyl ursolic acid (compound 3) was slightly contaminated with 3β-Oacetyl oleanolic acid (compound 4). Furthermore, the isolation of β-sitosterol and stigmasterol (compounds 5 and 6), methyl ursolate, and methyl oleanolate (compounds 8 and 9) as well as quercetin-3-O-β-D-glucopyranoside (isoquercetin) and quercetin-3-O-β-D-galactopyranoside (hyperoside) (compounds 11 and 12) as mixtures was in agreement with earlier studies (Furuya et al, 1987;Luhata and Munkombwe, 2015;Pereira et al, 2011).…”
Section: Resultssupporting
confidence: 87%
“…Previous studies on genus Ulmus reported the presence of various types of phytoconstituents like terpenoids (Martín-Benito et al, 2011), steroids (Martín-Benito et al, 2011), phenolics (Zhou et al, 2017), and polysaccharides (Lee et al, 2018). From a bioactivity standpoint, Ulmus species were reported to exhibit antibiotic (You et al, 2013), antifungal (Burden and Kemp, 1984), antioxidant (Bora et al, 2017;Joo et al, 2014;Mina et al, 2016), anti-inflammatory (Joo et al, 2014;Mina et al, 2016), hepatoprotective (Boudaoud-Ouahmed et al, 2015), neuroprotective (So et al, 2019), antiangiogenic (Jung et al, 2007), cytotoxic (Wang et al, 2004;Wang et al, 2006), anticancer (Hamed et al, 2015), and antiviral (Hamed et al, 2015) effects.…”
Section: Introductionmentioning
confidence: 99%
“…The connection of an acetyl group to Oh-23 was documented from the long rang correlation of Ch3-33 and 2h-23 with the carbonyl carbon C-32 [32]. According to the comparison of its properties and spectral data with the corresponding of structurally related compounds, it was identified as 23-acetyl-3β-Omethyloleanolic acid that is a new natural product [30][31][32][33].…”
Section: Compoundmentioning
confidence: 99%
“…UPLC-MS 2 spectra in negative mode show molecular ion peaks at: 169 and 301 [m-h]-corresponding to the mFs of C 7 h 6 O 5 , and C 14 h 6 O 9 ,, respectively. The UV spectral data of 1 and 2 exhibited an absorption band (λ max 217, 272 and 253, 367) characteristic for gallic and ellagic acids [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Depending on the comparison with their previously published spectral 1h and 13C-NmR data and Co-chromatography with the authentic samples, 11 and 12 were identified as gallic and ellagic acid, respectively [35 & 36].…”
Section: Compounds 11 and 12mentioning
confidence: 99%